Applied cognitive psychology - Olga. A Kistanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the characteristic features of cognitive psychology and its relation to linguistics. Cognitive psychology is a science which studies the perception of reality by a human being, and it has been developed during last few decades. Nowadays the information worked out by specialists in cognitive psychology is successfully used in linguistic studies of units of language. The perception of the real world by individuals is embodied in these units, and therefore a linguistic worldview is created.The units of language which are used to name human emotions are analysed from a psycho-cognitive perspective using the methods of cognitive psychology. While examining typical situations which provoke different emotions, we study their cognitive characteristics. As a result, a cross-disciplinary connection between cognitive psychology and linguistics is traced.